Girl online - Sugg, Zoe, 1990- (New York : Keywords Press/Atria, 2014)
But Noah has a secret too. One that threatens to ruin Penny's cover - and her closest friendship - forever.
I had no idea GirlOnline would take off the way it has - I can't believe I now have 5432 followers, thanks so much! - and the thought of opening up to you all about this is terrifying, but here goes...
Penny has a secret.
Under the alias GirlOnline, she blogs about school dramas, boys, her mad, whirlwind family - and the panic attacks she's suffered from lately. When things go from bad to worse, her family whisks her away to New York, where she meets the gorgeous, guitar-strumming Noah. Suddenly Penny is falling in love - and capturing every moment of it on her blog.
Keywords: Blogs -- Juvenile fiction; Online identities -- Juvenile fiction; Panic attacks -- Juvenile fiction; Teenage girls -- Juvenile fiction; Blogs -- Fiction; Online identities -- Fiction; Panic attacks -- Fiction; Teenage girls -- Fiction; Blogs; Online identities; Panic attacks; Teenage girls; Fiction; Juvenile works